Rhodium(I)‐Catalyzed Carboacylation/Aromatization Cascade Initiated by Regioselective C−C Activation of Benzocyclobutenones. (12th February 2018) - Sun, Tianwen; Zhang, Yuna; Qiu, Bo; Wang, Yafei; Qin, Yuting; Dong, Guangbin; Xu, Tao
Abstract: Described here is the first example of a rhodium‐catalyzed carboacylation/aromatization cascade of a C=O bond by C−C activation. In this transformation, a reactive rhodaindanone complex is regioselectively generated and adds across a C=O bond with subsequent elimination, thus providing a unique strategy to access a multisubstituted benzofuran scaffold. A diverse range of benzofuran analogues were obtained in good yields. Mechanistic studies show a tricyclic lactone was a viable intermediate. Application of this methodology to the total synthesis of C13‐deOH‐viniferifuran and C13‐deOH‐diptoindonesin G was achieved.